Protecting Attacks on Unmanned Aerial Vehicles using Homomorphic Encryption - Nayeem Ahmad Khan; Lilia Georgieva; Omar Ahmed Abdulkader; Mohammed Y. Alzahrani; Alawi M. Bamahdi; Ahmed H. Alahmadi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
With the exponential growth in the usage of unmanned aerial vehicles (UAV), often known as drones, for military, civilian, and recreational purposes. Security of internal communication modules and communication to the ground control station is considered the foremost challenge. Hacking into the system and attacking the internal communication devices with malicious code can disaster the vehicle's system. The need for having a secure communication channel between the internal modules of the vehicle and transmission of data to the ground control station is of utmost crucial. Existing mechanisms based on conventional encryption methods are highly suspectable to attacks as their keys can be broken by employing high computing power. Another challenge with these approaches is undesired high-level data communication latency affecting real-time communication. This study implements a homographic encryption-based technique for secure communication. In addition, we also propose a key regeneration algorithm based on pallier homomorphic encryption. Simulations were conducted using OMNET++ and Aerial Vehicle Network Simulator (AVENS). In this study 54 encryption attacks were collected from different sources. Compared to Digital Encryption Standard (DES) and Advanced Digital Encryption (AES), the proposed approach defended all the communication attacks between the UAV and the ground control station.